An Economic Analysis of the Financial Records of al-Qa'ida in Iraq - Bahney, Benjamin (RAND Corporation, 2010)
This monograph analyzes the finances of the militant group al-Qa'ida in Iraq in Anbar province during 2005 and 2006, at the peak of the group's power and influence. The authors draw on captured financial documents that give details on the daily financial transactions of one specific sector within Anbar province and of the financial transactions of the AQI provincial administration.